Adaptive PID based speed tracking control of DC motor - Husain, Mohd Husharilamri; Ahmad, Fauzi; Che Hasan, Mohd Hanif (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
This paper presents a study on the speed tracking control of DC Motor that is developed by using an Adaptive Proportional-Integral-Derivative (APID) control structure. The APID controller is used due to its ability to solve the drawback of conventional PID controller. DC motor system and proposed controller was simulated using MATLAB-Simulink software. Several tests such as step function, sine wave function and saw tooth function were used to examine the performance of the proposed controller. Several speed inputs were used to evaluate the performance of APID controller in term of percentage of overshoot (5%), rise time (0.25 second) and settling time (0.5 second). The results showed that the proposed control structure has the ability to achieve targeted speed control with a good response. The DC Motor test rig were used to investigate in real time experiment for the ability of the proposed controller structure by comparing simulation APID with experiment APID controller. The results show that the proposed control structure proves to be able to track the desire speed with acceptable error.